(untitled) (Regional aspects of productive forces development of Ukraine, 2019)
The article outlines the main trends in the development of the economy of the traditionally poorly developed agrarian Ternopil region in recent years. Disproportions in the industrial development of the region; the real reasons for the shifts in the region’s share in the total product of the country are detected, their connection with the modern socio-economic development of the country and its individual regions are defined. It was determined that the growth of the region’s share in the total product of the country is not accompanied by a proportional increase in the gross regional product, and therefore is not a consequence of progress in the economy of this region, but rather due to the reduction of the role of the occupied territories in the economy of the country. It was found that the progress of recent years is not yet a sign of a stable positive trend in development, as it is ensured by the largely extensive component of the economy - plant growing, and the related food industry. It is determined that the ineffectiveness of the structure of the economy of the region is reflected in the foreign trade balance, where the production of electrotechnical production dominates in exports, represented by only a few companies and products of agriculture. The urgent need to reform the structure of the economy based on a free competitive market has been identified in order to attract foreign investors, which would overcome the long-term depression and agrarian orientation of the economy of the region. The influence of the present level of development of the region on the life of the population is outlined and, therefore, the necessity of overcoming the contemporary contradictions of development is grounded in order to avoid degradation of poverty of the local population, its marginalization. The priority sectors of industry, which should become the basis for the formation of a new socio-economic base of the region, were determined.